SIMILES IN ENGLISH AND UZBEK AND THEIR ANALYSIS - Abdurakhmanova Mokhinur Bahromjon kizi (TADQIQOTLAR.UZ, 2023)
Abstract: In this article, the author analyzes in detail various synonyms in both languages and compares their usage and meaning. The article also discusses how to write synonyms and use them effectively in communication. The article begins by defining synonyms and showing their importance in language use. Then the author compares and contrasts various synonyms in English and Uzbek, explains their similarities and differences with examples and comments. The article also explores the subtleties of meaning that can be conveyed through the use of synonyms and how they can be used to add depth and complexity to language. Throughout the article, the author emphasizes the importance of understanding synonyms for effective communication and self-expression in both languages. Summarizing the main points made at the end of the article, it is emphasized the importance of continuing to study and research synonyms in English and Uzbek languages. Overall, the article is a valuable resource for anyone interested in language learning and the use of synonyms in communication.